Disaster Risk Reduction Efforts Through Flood Hazard and Resilience Assessment in the Coastal Area of Pasuruan, East Java - Noverma Noverma; Abd Halim Abd Halim (The Republic of Indonesia Defense University, 2025)
Coastal areas play a strategic role in the economy, ecosystem habitats, and areas with high socio-cultural value. However , coastal areas also face serious dangers from natural disasters, such as floods. Flood events often disrupt community activities, make roads impassable, displace residents, damage infrastructure, and negatively impact the social and economic well-being of communities, property losses and, in severe cases, loss of life . Addressing these issues requires effective strategies for coastal area management. This paper presents an analysis of the level of hazard and resilience of coastal areas to flood hazards . This study was conducted in the coastal area of Pasuruan, which frequently experiences seasonal flooding. The indicators used to analyze flood hazard and regional resilience are based on regulations established by relevant authorities and findings from previous related studies. Several parameters were measured, including flood inundation height , frequency of occurrence , and rainfall intensity (both high and low). Meanwhile, regional resilience was assessed using several indicators, including disaster risk management (DRM) policies and institutions , preparation of disaster risk assessments and documentation , development of early warning systems , mitigation efforts , and disaster education programs. The results revealed that flood hazard in the Pasuruan coastal area ranges from moderate to high , with four areas classified as high risk and three as moderate. Conversely, the resilience level of all areas is categorized as moderate. Furthermore, the findings of this study are expected to be taken into consideration in policymaking for coastal area management, particularly in reducing flood disaster risk.